On the electrical conductivity of alginate hydrogels - Kaklamani, Georgia (Regen Biomater, 2018)
Hydrogels have been extensively used in the field of biomedical applications, offering customizable natural, synthetic or hybrid materials, particularly relevant in the field of tissue engineering. In the bioelectronics discipline, hydrogels are promising mainly as sensing platforms with or without encapsulated cells, showing great potential in healthcare and medicine. However, to date there is little data in the literature which characterizes the electrical properties of tissue engineering materials which are relevant to bioelectronics. In this work, we present electrical characterization of alginate hydrogels, a natural polysaccharide, using a four-probe method similar to electrical impedance spectroscopy. The acquired conductance data show distinct frequency-dependent features that change as a function of alginate and crosslinker concentration reflecting ion kinetics inside the measured sample. Furthermore, the presence of NIH 3T3 fibroblasts encapsulated in the hydrogels matrix was found to alter the artificial tissue’s electrical properties. The method used provides valuable insight to the frequency-dependent electrical response of the resulting systems. It is hoped that the outcome of this research will be of use in the development of cell/electronic interfaces, possibly toward diagnostic biosensors and therapeutic bioelectronics.